2015
DOI: 10.1016/j.euprot.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phosphopeptide enrichment strategies for quantitative TMT analysis of complex network dynamics in cancer-associated cell signalling

Abstract: Defining alterations in signalling pathways in normal and malignant cells is becoming a major field in proteomics. A number of different approaches have been established to isolate, identify and quantify phosphorylated proteins and peptides. In the current report, a comparison between SCX prefractionation versus an antibody based approach, both coupled to TiO2 enrichment and applied to TMT labelled cellular lysates, is described. The antibody strategy was more complete for enriching phosphopeptides and allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…In our phosphoproteomic study, we identified nine distinct Kif26b phosphorylation sites on eight unique phosphopeptides, and all these sites mapped to serine or threonine residues ( Figure 1—figure supplement 2 and Supplementary file 1 ). In general, tyrosine phosphorylation is more dynamic than serine or threonine phosphorylation and tends to be underrepresented in large-scale phosphoproteomic studies ( Lombardi et al, 2015 ). We therefore examined whether Wnt5a-Ror signaling induces tyrosine phosphorylation of Kif26b in NIH/3T3 cells using an anti-phosphotyrosine antibody-based affinity pull-down approach.…”
Section: Discussionmentioning
confidence: 99%
“…In our phosphoproteomic study, we identified nine distinct Kif26b phosphorylation sites on eight unique phosphopeptides, and all these sites mapped to serine or threonine residues ( Figure 1—figure supplement 2 and Supplementary file 1 ). In general, tyrosine phosphorylation is more dynamic than serine or threonine phosphorylation and tends to be underrepresented in large-scale phosphoproteomic studies ( Lombardi et al, 2015 ). We therefore examined whether Wnt5a-Ror signaling induces tyrosine phosphorylation of Kif26b in NIH/3T3 cells using an anti-phosphotyrosine antibody-based affinity pull-down approach.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the methodologies available to enrich phosphopeptides in MM, the most widely practiced are immobilised metal ion chromatography (IMAC) (Thingholm and Larsen 2016a) and titanium dioxide (Thingholm and Larsen 2016b), and combinations thereof. In addition, fractionation protocols such as strong cation exchange (SCX) (Lombardi et al 2015), Fig. 10 Illustration of pathway signalling where phosphorylation signalling PTMs have been sequenced and annotated in melanoma tumours from patients hydrophilic interaction liquid chromatography (HILIC) (Boersema et al 2008) or basic reversed-phase chromatography can be utilised to increase coverage of the phosphoproteome (Batth et al 2014).…”
Section: Pathway Signalling and Protein Phosphorylationmentioning
confidence: 99%
“…Enrichment of the fraction of phosphorylated peptides utilised antibody precipitation coupled with TiO2 chromatography as described previously [ 26 ], with minor changes. For the anti-phosphotytrosine peptide immunoprecipitation, the antibody PT66 was replaced with pY1000 (Cell Signalling Technology, Hitchin, Hertfordshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…LC-MS/MS analysis was performed using an LTQ-Velos Orbitrap mass spectrometer (Thermo Fisher Scientific) as described previously [ 26 , 47 ]. A detailed description of data analysis can be found in the Supplementary Materials and Methods .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation